Uncoordinated dances associated with high reproductive success in a crane. (4th December 2018) - Takeda, Kohei F; Hiraiwa-Hasegawa, Mariko; Kutsukake, Nobuyuki
Abstract : Why do crane pairs dance? We showed uncoordinated dances associated with high reproductive success. Dance duration increased as the breeding season approached. The results partially supported the hypothesis that pair dances contribute to a pair bond. This is the first study to assess the role of pair dances in these animals. Abstract: Coordinated mutual displays by 2 individuals are believed to play important roles in social and sexual communication. Although previous studies have described mutual displays in birds, few have conducted quantitative analyses. To understand the role of mutual signals, we investigated the reproductive function of pair dances in the red-crowned crane ( Grus japonensis ). We used an information theory approach to quantify the characteristics of the pair dance and tested the classical "pair bond hypothesis, " which states that the elaborate dance is related to reproductive success. We found that characteristics of the pair dances were related to reproductive success, but the results were not always consistent with the predictions. Dance duration increased as the breeding season approached. However, the past reproductive success of an individual was negatively related to dance coordination (i.e., mutual information) of a pair. These results partially support the pair bond hypothesis, but more importantly, also suggest the need to define the vague concept of a "pair bond" in a biologically reasonable, measurable way.